RECONSTRUCTION OF PAST SETTLEMENTS IN AN AUDIO-VISUAL FORM - Adi, Ari Mukti Wardoyo; Izza, Nainunis Aulia (JURNAL SOCIUS, 2023)
People’s living in the past has always became a big question for everyone, not only archeology. Unfortunately the answers to these questions are sometimes difficult to understand directly by public. It takes an effort to provide an answer that is easily accepted by the public. One of them is to build the mindset of archeology students to be able to make archaeological research products that are more popular and useful. This study seeks to apply a project-based learning model to the Ancient Settlement course. Students are assigned to conduct research to reconstruct past settlements around Jambi based on their traces. The results of this research are then narrated in the form of a documentary and uploaded to an online video sharing service. Based on the research results, research products in the form of audio-visual media are more accessible to the general public. In addition, the current generation of “digital native” students also seems to find it easier to narrate research results through audio-visual media compared to textual narration.